Analisis Kesalahan Proses Morfologi pada Teks Tulis Siswa Kelas XI SMA Negeri 2 Parepare - Sarimah, Syaisatul; Mayong, Mayong; Yunus, Andi Fatimah (Panthera : Jurnal Ilmiah Pendidikan Sains dan Terapan, 2025)
This study aims to describe the error of morphological processes in the writing of written texts of grade XI students of SMA Negeri 2 Parepare, including affixation, reduplication, and pluralization. This type of research is qualitative descriptive research. The source of data from this study is student written texts. The focus of this research is: 1) morphological processes; 2) affixation errors; 3) reduplication errors; and 4) composition errors. The data collection technique is carried out by test technique. The instruments of this research are the researcher himself and the table. The results of the study showed that the morphological errors found consisted of: 1) affixation, including the use of prefixes, suffixes, and confixes that were not in accordance with the rules; 2) reduplication, in the form of improper repetition of words; and 3) pluralization, including writing compound words that are not in accordance with spelling. These findings indicate that students still have difficulty in applying morphological rules appropriately in formal writing. These findings show that students still have difficulty in applying morphological processes appropriately in writing.